A preliminary discussion on the notion of nationalism in Weber’s thought: Max Weber and his cogitation of nationalism - Özay, Mehmet; Saifuddin, Muhammad (İlmi Etüdler Derneği, 2022)
Nationalism is known as the product of the continuation of the Enlightenment in Western Europe. Although this ideology has an established place in studies on political science and has been a subject studied by political scientists, discussing whether the founding fathers of sociology had deliberated or not on this would be interesting. Max Weber seems to have developed an interest in the concept of nationalism after getting his professorship in economics. Once nationalism became a mainstream phenomenon among the world communities at the end of 20th century, Weber’s approach evoked interest among social scientists. This paper pays attention to Weber’s discussion of this notion in the context of German nationalism mostly based on the socio-political changes he witnessed. The basic question is what was Weber’s idea about nationalism and its place in his sociological and economic views? This paper tries to answer this question by comparatively going through sources. This preliminary work intends to review the ideas of Weber’s nationalism by engaging in the existing literature which is believed to be meaningful. This article limitedly addresses the reconstruction of Weber’s concept of nationality based on the availability of relevant data by revealing the academic discussion.